At the extreme limits of L-DOPA therapy: probable dopamine dysregulation and psychiatric complications in Parkinson’s disease - Oikarinen, Niko; Ottela, Emma; Rönkä, Jaana; Haanpää, Maria; Niemelä, Solja; Lees, Andrew John; Kaasinen, Valtteri (BMJ Publishing Group, 2026)
Background
Dopamine dysregulation syndrome (DDS) is an uncommon but debilitating complication of Parkinson’s disease (PD), characterised by a compulsive overuse of dopaminergic therapy. Most reported cases are male and involve daily oral levodopa (L-DOPA) intake between 2000 and 4000 mg.
Methods
We describe a female with young-onset PD who progressively escalated oral L-DOPA intake to a peak of 10 000 mg/day prior to subthalamic nucleus deep brain stimulation (DBS). A structured psychiatric assessment was performed after DBS. Whole-exome sequencing was conducted to evaluate possible genetic susceptibility.
Results
The patient developed compulsive medication use, impulse control disorders and gingival black pigmentation with near-total tooth loss. Classical hedonistic DDS features were absent. Following DBS, the L-DOPA dose stabilised at 1800 mg/day, but psychosis emerged, requiring hospitalisation. Genetic testing did not identify a pathogenic cause for early-onset PD; a rare missense variant of uncertain significance was detected without established clinical relevance.
Discussion
This case represents the highest sustained oral L-DOPA dose reported in PD. Despite lacking several core DDS features, the pattern of compulsive use suggests dopaminergic dysregulation. This case highlights limitations in current DDS criteria and suggests that contextual features, such as motor disability, psychological reinforcement and individual vulnerability, should be integrated into future refinements.